ANTI-HYPERGLYCEMIC AND ANTI-HYPERLIPIDEMIC POTENTIAL OF A POLYHERBAL PREPARATION “DIABEGON” IN METABOLIC SYNDROME SUBJECT WITH TYPE 2 DIABETES - Yadav, Dhananjay; Tiwari, Arvind; Mishra, Meerambika; Subramanian, Senthil S; Baghel, Usha Singh; Mahajan, Sunil; Bisen, P S; Prasad, GBKS (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: In the present study, “Diabegon” a poly-herbal preparation, with hypoglycemic activity, was evaluated for its preventive effect in metabolic syndrome subjects with type 2 diabetes and also to reveal its side effects, on liver and kidney. Materials and Methods: Type 2 diabetic subjects with metabolic syndrome (N=58) were categorized on the basis of age and fasting blood glucose. The grouping was as follows: Group I (35-50 yrs), Group II (51-65 yrs), Group III >65 yrs, Group IV FBS<145.9, Group V FBS>145. Each group was administered 4 gm of diabegon daily. Blood glucose levels, lipid profile, liver and kidney function of the subjects were regularly monitored within 3 months of interval to 18 months. Results: The reduction in fasting blood glucose level ranged from 12.3% (P<0.05) to 42% (P<0.001) after 18 month of therapy whereas in postprandial blood glucose, the decrease ranged from 28% (P<0.05) to 32% (P<0.05) after 18 month of therapy. Overall reductions in the individual parameters of the metabolic syndrome subjects were significantly higher in Group I. Cholesterol level decreased from 11% to 27.2% (P<0.001), triglyceride levels decreased from 24% to 55%, VLDL and LDL levels reduced by 60% & 54% respectively after 18 months of therapy. The HDL-C level increased in all groups. Moreover, diabegon administration for 1.5 years exhibited no alteration in liver and kidney function tests, which indicate its non-toxicity. Conclusion: Our study suggests that diabegon could be included as a preventive treatment in metabolic syndrome subjects with type 2 diabetes especially for long term treatment as it efficiently shows anti-hyperglycemic and anti-lipidemic effects with no adverse impacts on the liver and kidney.